Impact of Economic and Financial Development on Environmental Degradation: Evidence from Small Island Developing States (SIDS). Issue 2 (26th January 2019) - Seetanah, Boopendra; Sannassee, Raja Vinesh; Fauzel, Sheereen; Soobaruth, Y.; Giudici, Giancarlo; Nguyen, Anh Pham Huy
ABSTRACT: The aim of this study is to investigate the effect of economic and financial development (FD) on environmental degradation (ED) for a sample of 12 selected small island developing states for the period 2000–2016 using a panel vector autoregressive model which accounts for the issue of dynamism and endogeneity. Results from the long-run cointegration analysis confirmed that GDP per capita has a negative and significant impact on emissions implying that higher degree of economic development decreases the ED for our sample of island economies. The smaller long-run income elasticity as compared to the short run validates the environment Kuznets curve hypothesis. Although an insignificant impact of FD on CO2 emissions is reported, the joint effect of economic and FD on the environment indicates that FD will have an affirmative influence on the environment with island economies attaining a relatively good income level as well.